Gone before goodbye [large type] - Witherspoon, Reese, 1976-; Coben, Harlan, 1962- (Grand Central Publishing, 2025)
"Maggie McCabe is teetering on the brink. A highly skilled and renowned Army combat surgeon, she has always lived life at the edge, where she could make the most impact. And it was all going to plan--until it wasn't. Upside down after a devastating series of tragedies leads to her medical license being revoked, Maggie has lost her purpose, but not her nerve or her passion. At her lowest point, she is thrown a lifeline by a former colleague, an elite plastic surgeon whose anonymous clientele demand the best care money can buy, as well as absolute discretion. Halfway across the globe, sequestered in the lap of luxury and cutting-edge technology, one of the world's most mysterious men requires unconventional medical assistance. Desperate,and one of the few surgeons in the world skilled enough to take this job, Maggie enters his realm of unspeakable opulence and fulfills her end of the agreement. But when the patient suddenly disappears while still under her care, Maggie must become a fugitive herself"--